Gender imbalance in the field of providing forensic services for justice: current situation in ukraine and international experience - Agapova Оlena; Shpak, Yuliia (Archives of Criminology and Forensic Sciences, 2021)
Abstract. The article is dedicated to the issue of gender inequality in general, and in particular in the field of forensic expert support of justice, including the problem of vertical segregation of labor in leadership positions in state specialized institutions of Ukraine. The article outlines possible reasons for the existence of gender imbalance in the form of vertical segregation of labor in leadership positions in the field of employment and in the field of forensic expert support of justice, as well as examples of gender inequality manifestations. An analysis of previous researches of distinguished women scientists and representatives of civil society institutions as to the problem of gender imbalance in the field of education, professional self-determination and career growth has been carried out. A specific focus is drawn to particular manifestations of gender imbalance in science. At the same time, the analysis of legal regulations of national and international significance on counteraction to gender inequality in different areas of public life has been considered. The activity of central executive agencies regarding advancement of women in society and influence of initiated programs on counteraction to gender imbalance in the field of forensic expert support of justice is studied. Statistics on manifestations of possible vertical segregation of labor in leadership positions in state specialized institutions of Ukraine is provided. Examples of international organizations which activity has a wide range of influence and the ones which activity is aimed at improving the state of women forensic experts in the field of forensic expert support are outlined. The experience of such organizations for preventing and overcoming gender imbalance, as well as specific proposals for solving this problem are taken into consideration.